Inflation in the great recession and new keynesian models - Marco Del Negro; Marc P. Giannoni; Frank Schorfheide (Federal Reserve Bank of New York, 2013)
It has been argued that existing DSGE models cannot properly account for the evolution of key macroeconomic variables during and following the recent Great Recession, and that models in which inflation depends on economic slack cannot explain the recent muted behavior of inflation, given the sharp drop in output that occurred in 2008-09. In this paper, we use a standard DSGE model available prior to the recent crisis and estimated with data up to the third quarter of 2008 to explain the behavior of key macroeconomic variables since the crisis. We show that as soon as the financial stress jumped in the fourth quarter of 2008, the model successfully predicts a sharp contraction in economic activity along with a modest and more protracted decline in inflation. The model does so even though inflation remains very dependent on the evolution of both economic activity and monetary policy. We conclude that while the model considered does not capture all short-term fluctuations in key macroeconomic variables, it has proven surprisingly accurate during the recent crisis and the subsequent recovery.
Keywords: C52; E31; E32; E37; 330; Great Recession; fundamental inflation; DSGE models; Bayesian estimation